Organic Polymer Dots as Photocatalysts for Visible Light‐Driven Hydrogen Generation. (8th September 2016) - Wang, Lei; Fernández‐Terán, Ricardo; Zhang, Lei; Fernandes, Daniel L. A.; Tian, Lei; Chen, Hong; Tian, Haining
Abstract: For the first time, organic semiconducting polymer dots (Pdots) based on poly[(9, 9′‐dioctylfluorenyl‐2, 7‐diyl)‐co‐(1, 4‐benzo‐2, 1′, 3 thiadiazole)] (PFBT) and polystyrene grafting with carboxyl‐group‐functionalized ethylene oxide (PS‐PEG‐COOH) are introduced as a photocatalyst towards visible‐light‐driven hydrogen generation in a completely organic solvent‐free system. With these organic Pdots as the photocatalyst, an impressive initial rate constant of 8.3 mmol h −1 g −1 was obtained for visible‐light‐driven hydrogen production, which is 5‐orders of magnitude higher than that of pristine PFBT polymer under the same catalytic conditions. Detailed kinetics studies suggest that the productive electron transfer quench of the excited state of Pdots by an electron donor is about 40 %. More importantly, we also found that the Pdots can tolerate oxygen during catalysis, which is crucial for further application of this material for light‐driven water splitting.